Teaching Modules of Kurikulum Merdeka Based on Neurofeedback NeuroSky Integrated with Subak Bali Culture for Teachers in Densely Populated Areas - I Wayan Kertih; I Wayan Wiarta; Adrianus I Wayan Ilia Yuda Sukmana (International Journal of Community Service Learning, 2026)
The low quality of learning in Tukadsumaga Village, particularly in the use of innovative technology and the integration of local cultural values, affects the learning process. This community service activity aims to develop a teaching module based on NeuroSky Neurofeedback technology integrated with Balinese Subak culture, which is expected to improve learning effectiveness, teacher skills, and the preservation of local culture. This activity used a mixed-methods design, combining quantitative and qualitative methods, involving 55 teachers and educators from various schools in Tukadsumaga Village. Data were collected through observation, interviews, focus group discussions (FGDs), pre-tests, and post-tests. The results of this activity demonstrate the success of the NeuroSky technology-based teaching module development program integrated with the Balinese Subak culture in improving the quality of education. Therefore, the program successfully increased achievement in both main aspects, with post-test results significantly exceeding the set targets. This technology-based approach and local culture can be an effective strategy in improving the quality of education based on the Independent Curriculum   that can be adopted in other regions with appropriate contextual adaptations.